Radiation Therapy as an Alternative Treatment for Desmoid Fibromatosis. Issue 9 (September 2018) - Hong, A.M.; Jones, D.; Boyle, R.; Stalley, P.
Abstract: Aim: To determine the outcome after radiation therapy for desmoid fibromatosis. Materials and methods: A retrospective review of 50 patients treated between 1988 and 2016 in a specialised bone and soft tissue tumour clinic. Results: The median age at the time of radiation therapy was 36.8 years (range 15.1–69.0) and the median follow-up time was 51 months. Forty-three patients underwent radiation therapy as the definitive treatment with a median dose of 56 Gy (range 30–58.8 Gy). The median dose for the seven patients treated with postoperative radiation therapy was 50.4 Gy (range 48–56 Gy). Eleven patients (22%) developed progressive disease after radiation therapy at a median time of 41 months (range 12–113 months). The recurrences were within the radiation therapy field in four patients and outside the field in seven patients. One patient developed a radiation-induced malignancy 20 years after treatment. Conclusions: Radiation therapy is an alternative treatment in the management of desmoid fibromatosis. It should be considered in patients for whom surgical resection is not feasible, or as adjuvant therapy after surgery with involved margins where any further recurrences would cause significant morbidity. Highlights: Series of 50 patients with desmoid fibrosis treated with radiation therapy at a dedicated bone and soft tissue tumour centre. Long-term follow-up with a response rate of 78%. One patient developed radiation-induced malignancy 20 years after radiation therapy.